Teacher supervision as a policy implementation of school heads in improving teacher performance at MTSN 1 and SMPN 1 Tulungagung - Syarifuddin, Ahmad; Akhyak, Akhyak; Patoni, Achmad; Maftukhin, Maftukhin (Technium Social Sciences Journal, 2021)
Teacher is one of the most important aspects of the learning process. This important role requires teachers to continue to improve their performance in order to be able to provide the best learning. The various policies taken by the principal are expected to be able to improve the teacher performance. The six competencies of school principals, the supervisory competence must also be mastered by the principal. Teacher supervision is a process of guidance carried out by the principal of teachers and other school personnel who are responsible for the learning process so that students can learn effectively and increase learning achievement. This study uses a qualitative approach, a type of case study with a multicase design. The results showed that teacher supervision as the implementation of the principal’s policy by providing administrative supervision and direct supervision, involving teachers in seminars, workshops or scientific discussions related to improving the quality of learning and forming a special supervision team to assist the principal’s duties.